2023
DOI: 10.3389/fpls.2022.1082513
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of marker trait associations for grain micro-nutrients and thousand grain weight under heat and drought stress conditions in wheat

Abstract: IntroductionWheat is grown and consumed worldwide, making it an important staple food crop for both its calorific and nutritional content. In places where wheat is used as a staple food, suboptimal micronutrient content levels, especially of grain iron (Fe) and zinc (Zn), can lead to malnutrition. Grain nutrient content is influenced by abiotic stresses, such as drought and heat stress. The best method for addressing micronutrient deficiencies is the biofortification of food crops. The prerequisites for marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 112 publications
(143 reference statements)
0
7
0
Order By: Relevance
“…The significant LD block size for the complete genome in the current investigation is 3.49 Mb. The LDs for the subgenomes for the A, B, and D genomes were determined to be 2.48 Mb, 4.29 Mb, and 3.82 Mb, respectively [28]. In agreement with this, Pang et al [52] reported a huge LD block size of 4.4 Mb.…”
Section: Genome-wide Association and Candidate Gene Identificationmentioning
confidence: 60%
See 4 more Smart Citations
“…The significant LD block size for the complete genome in the current investigation is 3.49 Mb. The LDs for the subgenomes for the A, B, and D genomes were determined to be 2.48 Mb, 4.29 Mb, and 3.82 Mb, respectively [28]. In agreement with this, Pang et al [52] reported a huge LD block size of 4.4 Mb.…”
Section: Genome-wide Association and Candidate Gene Identificationmentioning
confidence: 60%
“…Seeds harvested from field experiments conducted during the 2020-2021 and 2021-2022 Rabi seasons at the Indian Council of Agricultural Research (ICAR) Institute in New Delhi (28.6550 • N latitude, 77.1888 • E longitude, elevation 228.61 m) were utilised in our laboratory studies, representing the two distinct seasons. More information about the origins (Supplementary Table S1) and population structure has been published by Devate et al [28].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations